Effects of Low Doses of L-Carnitine Tartrate and Lipid Multi-Particulate Formulated Creatine Monohydrate on Muscle Protein Synthesis in Myoblasts and Bioavailability in Humans and Rodents - Fielding, Roger A.; Rivas, Donato; Grosicki, Gregory J.; Ezzyat, Yassine; Ceglia, Lisa; Price, Lori Lyn; Bellamine, Aouatef (Mdpi, 2021)
The primary objective of this study was to investigate the potential synergy between low doses of L-carnitine tartrate and creatine monohydrate to induce muscle protein synthesis and anabolic pathway activation in primary human myoblasts. In addition, the effects of Lipid multi-particulates (LMP) formulation on creatine stability and bioavailability were assessed in rodents and healthy human subjects. When used individually, L-carnitine tartrate at 50 mu M and creatine monohydrate at 0.5 mu M did not affect myoblast protein synthesis and signaling. However, when combined, they led to a significant increase in protein synthesis. Increased AKT and RPS6 phosphorylation were observed with 50 mu M L-carnitine tartrate 5 mu M creatine in combination in primary human myoblasts. When Wistar rats were administered creatine with LMP formulation at either 21 or 51 mg/kg, bioavailability was increased by 27% based on the increase in the area under the curve (AUC) at a 51 mg/kg dose compared to without LMP formulation. Tmax and Cmax were unchanged. Finally, in human subjects, a combination of LMP formulated L-carnitine at 500 mg (from L-carnitine tartrate) with LMP formulated creatine at 100, 200, or 500 mg revealed a significant and dose-dependent increase in plasma creatine concentrations. Serum total L-carnitine levels rose in a similar manner in the three combinations. These results suggest that a combination of low doses of L-carnitine tartrate and creatine monohydrate may lead to a significant and synergistic enhancement of muscle protein synthesis and activation of anabolic signaling. In addition, the LMP formulation of creatine improved its bioavailability. L-carnitine at 500 mg and LMP-formulated creatine at 200 or 500 mg may be useful for future clinical trials to evaluate the effects on muscle protein synthesis.
Keywords: muscle; carnitine; creatine; protein synthesis